2022
DOI: 10.1057/s41269-022-00242-x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfied unlike me? How the perceived difference with close network contacts prevents radical and protest voting

Abstract: Fitting with a common scheme across European democracies, the last election in Belgium led radical (left and right) parties to increase their vote share. One of the key drivers of the radical vote is political dissatisfaction (Droste 2011). Yet, the latter does not always translate into radical or protest voting behaviors. Using the 2019s RepResent Belgian Elections Study, we show the moderating effect of close social contacts in this relationship. For dissatisfied voters who believe that most contacts are sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
1
0
1
Order By: Relevance
“…However, similar to the literature on citizens' preferences for democracy (König et al 2022), the empirical results remain fragmented and are not always consistent when it comes to the ideological roots of referendum support. Somehow connected to the dissatisfied thesis, what recent studies have observed is instead a strong cleavage based on radical and moderate party preferences, between people voting for radical parties and those moderate voters opting for mainstream parties embedded in traditional left or right ideologies (Paulis and Ognibene 2022). People casting vote in favour of parties located at the extreme, both on the right and left sides of the political spectrum, are more favourable to referendums (Rojon and Rijken 2020;Schuck and de Vreese 2015).…”
Section: Support For Referendums Among Votersmentioning
confidence: 97%
“…However, similar to the literature on citizens' preferences for democracy (König et al 2022), the empirical results remain fragmented and are not always consistent when it comes to the ideological roots of referendum support. Somehow connected to the dissatisfied thesis, what recent studies have observed is instead a strong cleavage based on radical and moderate party preferences, between people voting for radical parties and those moderate voters opting for mainstream parties embedded in traditional left or right ideologies (Paulis and Ognibene 2022). People casting vote in favour of parties located at the extreme, both on the right and left sides of the political spectrum, are more favourable to referendums (Rojon and Rijken 2020;Schuck and de Vreese 2015).…”
Section: Support For Referendums Among Votersmentioning
confidence: 97%
“…Тогда с большей вероятностью они будут избегать протестного голосования. Отсюда специфику недовольства и/или голосования необходимо изучать с точки зрения не только личностных мотиваций, но и сетей социального взаимодействия [Paulis, Ognibene 2022].…”
Section: '01 власть 117unclassified